2019
DOI: 10.7717/peerj.7434
|View full text |Cite
|
Sign up to set email alerts
|

Use of factor scores in multiple regression analysis for estimation of body weight by certain body measurements in Romanov Lambs

Abstract: The study investigates the solution of the multicollinearity between certain body measurements of Romanov lambs and prediction of the body weight of Romanov lambs using the thus calculated factor analysis scores and a multiple regression model. For this purpose, the body measurements (wither height (WH), croup height (CH), body length (BL), chest depth (CD), chest circumference (CC), chest width behind shoulders (CWS) and head length (HL)) and body weight (BW) of 6-month-old 50 Romanov lambs born in 2015 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
(22 reference statements)
0
15
1
Order By: Relevance
“…To analyze the collected data, descriptive analysis was used to find the current practices and multiple regression analysis was used to establish the relationships between dependent and independent variables. The multiple regression analysis was used in the study as one of the methods to describe the relationship between one dependent variable and multiple independent variables (Jomnonkwao et al, 2020;Tahtali, 2019). For descriptive analysis, mean value in between 1 and 2.99 is considered low, 3 and 3.99 is moderate, and 4 and 5 is high.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the collected data, descriptive analysis was used to find the current practices and multiple regression analysis was used to establish the relationships between dependent and independent variables. The multiple regression analysis was used in the study as one of the methods to describe the relationship between one dependent variable and multiple independent variables (Jomnonkwao et al, 2020;Tahtali, 2019). For descriptive analysis, mean value in between 1 and 2.99 is considered low, 3 and 3.99 is moderate, and 4 and 5 is high.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the Bartlett"s test value (5387.696; P < 0.001) and KMO value (0.934) obtained to test the divisibility of the correlation matrix into factors, the data was determined to be suitable for factor analysis. Therefore, obtaining significant results from both tests shows that the data are suitable for factor analysis (Tahtali, 2019). Both models were valid and reliable with no autocorrelations (D-W of 1.889) or multicollinearity (VIF ˂ 2) effects.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, to explore the correlation between cashmere yield and growth traits of Liaoning cashmere goats, the breeding goal of indirectly increasing cashmere yield can be achieved by selecting the performance values of the corresponding traits that are easy to measure. In the breeding practice of domestic animals such as lambs [ 23 , 24 ], sheep [ 18 ] and goats [ 7 , 25 ], cattle [ 19 ], poultry [ 20 , 26 ], and aquaculture animals [ 10 , 27 ], countries use the correlation regression analysis method and correlation coefficient analysis between the traits to explore the phenotypic correlation and the direct relationship between the target traits, and the analysis of the degree of indirect influence accelerates the breeding process of the corresponding animals. At the same time, it is indicated that cashmere goat breeding should not only consider cashmere yield and growth traits but also need to consider the effects of other factors such as nutrient levels and feeding management on production performance.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a stepwise regression analysis was performed, and statistical data were used to investigate tolerance and VIF values, demonstrating the absence of multicollinearity (VIF < 10) among the variables. However, many studies with multicollinearity used factor score analysis to solve the problem [ 22 , 23 , 24 , 28 ]. Therefore, factor analysis was used in this study.…”
Section: Discussionmentioning
confidence: 99%